STRATEGI PEMBELAJARAN BAHASA ARAB MELALUI METODE QIRA’AH JAHRIYYAH PADA MASA PANDEMI COVID-19 (Karya Ilmiah Mahasiswa (KIMA), 2022)
The implementation of social distancing policies during the Covid-19 pandemic which has an impact on the world of education from elementary to university levels. This pandemic period requires the learning system to be replaced with online learning so that the learning process continues. Educational activities carried out online in the midst of this epidemic have many obstacles that become obstacles in the smooth implementation of learning both felt by teachers, students and parents of students. This research is a field research on students of Madrasah Tsanawiyah Negeri Belopa, Luwu Regency, which aims to find out about students' Arabic reading methods or abilities. This research is a quantitative research. This study emphasizes the analysis on numerical data which are processed by statistical methods. Qira'ah Jahriyyah learning strategy during the Covid-19 pandemic, student learning in class is very limited by time, the distance between one student and another. With this strategy, students are less able to understand learning, so the teacher takes actions such as using several applications used in learning such as sending videos or voice recordings when reading Arabic texts and continuing at each student's home to understand the lessons given by the teacher.